Is a verification phase useful for confirming maximal oxygen uptake in apparently healthy adults? A systematic review and meta-analysis - Costa, V. A. B.; Midgley, A. W.; Carroll, S.; Astorino, T. A.; de Paula, T.; Farinatti, F.; Cunha, F. A. (PLOS ONE, 2021)
Background: The `verification phase` has emerged as a supplementary procedure to traditional maximal oxygen uptake (VO2max) criteria to confirm that the highest possible VO2 has been attained during a cardiopulmonary exercise test (CPET).